The role of traditional leadership in combating Gender-Based Violence in Vhembe District Municipality, Limpopo Province - Mokgonyana, Kgathane Veronica (My University, 2024)
The study explores the role of Traditional Leaders in combating Gender Based Violence (GBV) in Vhembe District in Limpopo Province. The qualitative research approach was applied in this study to investigate how Traditional Leaders are fighting GBV in the areas where they have authority. A structured questionnaire was distributed to the targeted respondents, to get their knowledge and understanding regarding how traditional leaders are combating GBV in their communities. The sample size was 16 respondents. Data for this study were analysed through thematic analysis. The study found that traditional leaders have a significant influence on the community in encouraging them to fight the pandemic of GBV. The study also revealed that there is a weak working relationship between government departments and the House of Traditional Leaders in the fight against Gender – Based Violence. Moreover, Traditional Leaders are faced with challenges on the funding of programmes that are geared towards combating GBV in their communities. Ten out of eleven traditional leaders had collaborative relations with Non-Profit Organisations that assist victims of GBV. The research also revealed that Traditional Leaders are not much involved in government processes for planning of programmes, budget allocation and projects implementation. Based on these research findings, the study proposed strategies aimed at harmonizing the relations between government and traditional leaders in the fight against GBV. The study further proposes joint planning of government, traditional leaders and other stakeholders in adopting strategies that will lead to increased and sustained efforts to fight GBV in communities and particularly in Vhembe District. Based on the study findings, it became evident that traditional leaders still possess sustained authority over their communities, and they are relevant in leading the fight against GBV, in collaboration with the government and other stakeholders
Thesis (MPAM.) -- University of Limpopo, 2024
Keywords: Traditional Leaders; Gender Based Violence; Communities; Non-Profit Organisations; Government; Community leadership; Leadership; Gender-based violence; Community leadership -- South Africa -- Limpopo